Perceived racial discrimination and polysubstance use among African American and Afro-Caribbean adults: Results from the National Survey of American Life. Issue 4 (4th November 2022) - Mattingly, Delvon T.; Fleischer, Nancy L.; Colston, David C.; Mezuk, Briana
Abstract: This study examined the relationship between perceived racial discrimination (PRD) and patterns of substance use. Data come from the 2001–2003 National Survey of American Life ( N = 3, 589). PRD was derived from the Major Experiences of Discrimination Scale. Multinomial logistic regression estimated the relationship between PRD and patterns of substance use (i.e., never/former, single-substance, dual-substance, and polysubstance [3+ substances]) based on six substances; effect modification by ethnicity and sex was assessed by stratification. Study findings indicated that PRD was associated with greater odds of lifetime and current polysubstance use. Results from the effect modification analyses suggested differential associations by ethnicity and sex.